126k views
3 votes
For the following geometric sequence find the explicit formula: {-1, 3, -9,...}

User Stambikk
by
4.8k points

2 Answers

2 votes
multiplies by -3 every time
User Masoud Dadashi
by
4.5k points
0 votes

Answer:


a_(n) = - 1
(-3)^(n-1)

Explanation:

The explicit formula for a geometric sequence is


a_(n) = a
(r)^(n-1)

where a is the first term and r the common ratio

Here a = - 1 and r = 3 ÷ - 1 = - 3 , thus explicit formula is


a_(n) = - 1
(-3)^(n-1)

User Eathen Nutt
by
4.8k points